PENCEGAHAN OVER HEATING MESIN MOBIL HILUX DOUBLE CABIN - Marjuki, Ismael; Epriyandi, Epriyandi (Pengelola Jurnal Politeknik Negeri Ketapang, 2021)
Human needs are increasing in the world of transportation, especially for two-wheeled vehicles or more. In the automotive world, especially cars, there are various kinds of systems that work. These systems work in conjunction with one another so that if one of these systems is damaged, the car will be damaged. such as damage to the cooling system which can cause overheating of the engine. Overheating is the occurrence of excessive heat above the engine's working temperature which is caused by damage to one of the components of the cooling system. The occurrence of overheating in the Hilux double cabin car engine is caused by a lack of coolant, the thermostat is not functioning properly, the radiator cap is leaking, the inlet and outlet hoses are cracked and the water pump is damaged. To avoid damage, preventive maintenance must be carried out. Check the coolant in the radiator reservoir every 1 week and change the fluid every 80,000 km. Thermostat replacement every 80,000 km. Replacement of radiator caps every 80,000 km. Replacement of inlet and outlet hoses every 80,000 km. Water pump replacement every 80,000 km. and a v-belt replacement every 60,000 km.